Frequency and Dynamics of Non-motor Symptoms Presentation in Hispanic Patients With Parkinson Disease - Sánchez-Martínez, Claudia Marisol; Choreño-Parra, José Alberto; Placencia-Álvarez, Noel; Nuñez-Orozco, Lilia; Guadarrama-Ortiz, Parménides (Frontiers in Neurology, 2019)
The clinical phenotype of Parkinson’s disease (PD) encompasses a wide range of non-motor symptoms (NMS) compromising the quality of life of affected patients. Currently, information about NMS in PD is scarce among Hispanic populations. Furthermore, few studies have reported the temporal pattern of NMS presentation. We conducted a cross-sectional study aimed to describe the frequency and time of NMS occurrence in Hispanic patients with PD using the self-completed NMS questionnaire (NMSQuest). Participants were interrogated about the time of each NMS presentation respect to the onset of motor symptoms. The frequency of NMS was described according to gender, age at disease onset, disease duration and Hoehn and Yahr (H&Y) stage. We enrolled 120 patients, 73.33% males and 26.66% females, with a mean age of 63.33±8.60 years. All the participants presented at least 1 NMS. The median number of NMS per patient was 12. The most frequent NMS domains were miscellaneous, urinary tract, sleep/fatigue, and gastrointestinal tract symptoms, with no significant gender differences. The most frequent individual NMS were nocturia, urinary urgency, feeling sadness, and constipation. Any patient reported NMS before the onset of motor manifestations. The pattern of occurrence of NMS domains in our population was as follows: attention/memory, cardiovascular, gastrointestinal tract, perceptual problems/hallucinations, mood/cognition, urinary, miscellaneous, sleep/fatigue, and sexual function. Nausea/vomiting was the earliest symptom observed in all patients, whereas sexual dysfunction and changes in interest for sex were the last symptoms to occur. We found no differences in the total number and frequency of NMS between participants grouped according to their age at disease onset. Conversely, patients with a duration of disease >10 years reported a higher frequency of NMS compared to participants with a duration of disease < 10 years. The total number of NMS per patient increased as the HY stage progressed. The proportion of patients presenting symptoms of the gastrointestinal tract, urinary tract, mood/cognition, cardiovascular, and sexual function domains was higher in the HY 4-5 group. Our study provides relevant data to improve our understanding of NMS in PD, which may contribute to anticipate and plan diagnostic and therapeutic strategies among Hispanic PD patients.